The Work of Adele Wiseman - Zipursky, Freda S. (My University, 1980)
This thesis is a study of the work of Adele Wiseman, with particular emphasis on the analysis of her novels, The Sacrifice and Crackpot. The Eastern European Jewish background of the writer, with which she identifies strongly, as well as her Winnipeg roots, are a focus of special attention for the purpose of interpreting her work within its appropriate cultural context. The development of similar themes and symbols, and apparent differences in perspective and style in the two novels are examined. Adele Wiseman's continuing social, political, and moral concerns are analyzed, and her ideas and observations about the creative process are noted. An attempt has been made to demonstrate the integral relationship of these concerns and ideas to her literary creativity.
Keywords: English Language and Literature; English Language and Literature